Sistem Pemantauan Gas Benzena dengan Aplikasi Blynk - Hidayanti, Fitria; Lestari, Kiki Rezki; Kusumo, Donni Indra (Universitas Nurul Huda, 2021)
Benzene gas is a material widely used in the laboratory as a solvent. Benzene gas can be harmful to people. Therefore, this study aims to measure and monitor benzene gas levels with the Internet of Things (IoT) platform as a monitoring and notification system on android smartphone devices. The sensor used is MS 1100 to detect benzene gas and transmit input signals. The NodeMCU microcontroller processes these signals. This wifi module in NodeMCU sends the sensor’s value to the Blynk IoT platform to display in graph form. This value is processed under the program and it meets the setpoint then the system provides notifications to users through the Blynk application on android smartphone devices as well as activating buzzer and exhaust fans in the laboratory room. The result showed that monitoring of benzene gas in the laboratory as 0.17 ppm.